Térkategóriák és egyenlőtlenségek az információs társadalmi átalakulás korában - Jakobi, Ákos (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
There are more and more practical experiences confirming that processes affecting spatial differences are altering in certain elements in the information age. By the appearance of .the new innovations of information and communication technologies a transformation process has got started, which have changed our opinion on spatiality. From the complex system of interconnectedness the dimensions of digital divide, or the circumstances of inequalities of development and competitiveness can be traced out. Spatial cathegories went through significant changes in interpretation, which have influenced also regional competitiveness and inequalities. According to our experiences, inherited spatial differences may be repeated in the information age, however, the revaluation of the role of distance or place can put this question into a new light. The paralell existance of traditional and new inequalities is one of the most important phenomenon of the information age.